Humanizar e expandir : uma genealogia da segurança pública em São Paulo - Marques, Adalton José (2017)
In this thesis, I examine the emergence of a democratic and humanist reasoning in the core of the public security thought, elaborated in São Paulo at the end of the Military Dictatorship. I try to explain how this reasoning, which I call the “triptych public security – democracy – human rights”, has not only made possible but also encouraged the expansion of the penal system (police, judiciary, and penitentiary sections). To do so, I organized the thesis in four chapters that follows this process. In the first chapter, I describe the inception of this democratichumanist concerns, presenting the discursive formations that prevent addressing the problem of criminality without enunciating the problem of marginality (poverty, unemployment, socioeconomic inequality). In the second chapter, I expose the way in which the democratic and humanist government of André Franco Montoro, sustained by these discursive formations, quickly abandoned his agenda of structural transformations for public security, gave way to controversial agenda for police forces (temporary arrest and Operation Pole), and also promoted the quantitative and qualitative expansion of the control institutions that he sought to democratize and humanize. In the third chapter, I examine a discourse line external to the Montoro government, although it continually reinforced it: the Sociology of Violence. Having more time to forge a robust reasoning, the Socioloogy of Violence coined its own theoretical enemy (the notorious thesis of the relationship between poverty and crime) defining methodological rules for research on violent criminality, and erecting the centrality of the institutional problem for democratic policies of public security. Finally, in the fourth chapter, I explained the way in which this democratic and humanist reasoning, made science by the Sociology of Violence, became the guidelines for the Paulista and federal policies of human rights and public security after the Carandiru Massacre. The policy of federalization of human rights, promoted by President FHC and closely followed by his co-religionist in São Paulo, Mário Covas, resulted in the intensification of incarceration and police expansion, mainly the militarized one. President Lula's next federal administration further intensified these policies, adding to them the grammar of citizen participation and creating the Growth Acceleration Program of public security, through which we came to live the apex of punitive developmentalism. Although the diachronic character of this thesis may suggest a historiographical approach to the material analyzed, I must say that it is an anthropologicalgenealogical construct, insofar as I consider the knowledge that has been buried in this process as adequate suspicions against the consolidated narratives.